2014
DOI: 10.2320/matertrans.m2014115
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Observation of Grain Boundary Sliding of ODS Ferritic Steel in High Temperature Tension

Abstract: High-temperature tensile deformation was performed using ODS ferritic steel, which has grain structure largely elongated and aligned in one direction, in the direction perpendicular to the grain axis. In the superplastic region II, two-dimensional grain boundary sliding (GBS) was achieved, in which the material did not shrink in the grain-axis direction and grain-boundary steps appeared only in the surface perpendicular to the grain axis. In this condition, a classical grain switching event was observed. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Specifically, dislocation activities were limited within mantles in region II/III but also observed in cores in region III. Significant GBS was also detected in region III, where small amount of GBS had previously been identified [18].…”
Section: Mechanical Behaviormentioning
confidence: 79%
See 4 more Smart Citations
“…Specifically, dislocation activities were limited within mantles in region II/III but also observed in cores in region III. Significant GBS was also detected in region III, where small amount of GBS had previously been identified [18].…”
Section: Mechanical Behaviormentioning
confidence: 79%
“…Specifically, (i) the dislocations adopted a parallel alignment below region II instead of a complicated substructural evolution above region II/III, and (ii) dislocations below region II cannot be maintained without dispersion particles but those above region II/III are preserved alone after deformation. These differences between dislocation characteristics imply that another 18 dislocation accommodation operates in regions I and II. Xun and Mohamed concluded that the mechanism was the Ball-Hutchison type [3], which is accommodated by transgranular slippage and the pile-up of dislocations.…”
Section: Verification Of the Mechanism By Reviewing Past Studiesmentioning
confidence: 97%
See 3 more Smart Citations